Pelatihan Tech for Kids untuk Meningkatkan Kesadaran dan Peminatan Siswa tentang Rekayasa sebagai Jalur Karir - Deny Nusyirwan; Lukman Hamdani; Hardyansah Hardyansah; Muhammad Idris Syahputra; Marzuki Marzuki; Ilham Fikri; Tauriq Fuji Nur Akbar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Riau Islands Province requires the readiness of Human Resources (HR) who are able to compete in the global market, with its position next to neighboring Malaysia and Singapore can be an advantage and also a weakness if HR is unable to compete globally. Therefore, the electrical engineering department with the tech for kids program seeks to provide personality and technical skills training to elementary and secondary school children in the coastal areas of Tanjung Pinang. The tech for kids program focuses on understanding the engineering design process to be able to produce innovations and products that are able to compete globally and on target. Activities that are carried out routinely weekly are accompanied by students as facilitators who will assist the supervisor during the training. The pattern of training and learning that integrates the technical ability of design using Autodesk inventors with non-technical forms of the ability to think innovatively, critically, and be able to work together with friends in a group will create a superior personality in the era of the industrial revolution 4.0. The training results obtained satisfactory results where students can attend the training enthusiastically and still remain enthusiastic until the end of the activity. The limited use of computer equipment is not an obstacle in the implementation in the field because students are able to manage training schedules well.